Impactos das reformas trabalhista e da previdência em trabalhadores adultos - Evaristo, Arlei Olavo (2021)
The changes in Brazilian legislation, which took place after the 2003-2016 cycle, decreed the end of the neodevelopmentalist period, whose societal concern gives way to the neoliberal proposal, marked by a fiscal austerity policy, began to gain strength, with the central concern being the market and corporate profits and generate a primary surplus, destined to pay interest and services on the public debt. Changes in the guidelines of the Brazilian public administration were implemented with Constitutional Amendment 95/2016, the Labor Reform (Law 13,467/2019) and Constitutional Amendment 103/2019, which deals with social security reform, substantially transform the world of work, impacting on labor relations, in the living and working conditions of the Brazilian population. The present work proposes to analyze the impacts of the labor and social security reforms on work, unemployment and retirement of workers, mainly adults, prioritizing the analysis of population indicators from 45 to 60 years of age. This is a study of a social nature, with a quali-quantitative approach. Data collection was carried out through document analysis and survey of indicators in public databases with sociodemographic information. Data analysis is guided by the qualitative and statistical approach described. The ethical aspects of this investigation are guided by Resolution No. 510/2016. The results show great impacts on the investigated indicators, mainly in relation to unemployment, informal work and discouragement.